Hi,

I hope someone can help. I was hoping that someone can provide a proof for why 1 + tan^2θ does not equal sec^2θ. I know that I can have θ equal something, and then see if both sides end up being the same e.g. 1 + tan^2(pi/3) = sec^2(pi/3) .... 1 + (√3)^2 = (1/(1/2))^2 ... 4 = 4.

While this case above (when θ = pi/3) proves that the equation is right, I don't think this proves why this is right for all cases of θ. Can someone help provide a more general proof for why the LS equals the RS?

Sincerely,

Olivia